Analysis on numerical simulation and fracture mechanics model of water inrush of floor with hidden faults under dynamic and static loads - Zhao, Xianwei; Yang, Dengfeng; Zhu, Yanyan; Zeng, Aiping (Frontiers in Earth Science, 2024)
The mining activation of hidden faults under dynamic and static loads is an important reason for the occurrence of floor water inrush disasters in deep coal seam mining. The formation and evolution mechanism of water inrush channel caused by mining on the floor of hidden faults were analyzed through numerical simulation, from the perspective of fracture mechanics, a model was constructed to explore the influence of combined dynamic and static loads on the propagation of water with cracks. A conclusion was drawn that the effects of mining stress and confined water have led to rapid expansion of hidden fault cracks and significant improvement in permeability, at the same time, the confined water in the hidden fault also has a scouring and expansion effect on the cracks, accelerating their development speed. There are spatial and temporal differences in the penetration patterns of hidden faults at different positions of floor, and the closer it is to the goaf, the more likely it is to experience activation of hidden faults and water inrush. When there are multiple hidden small faults in the floor, there is an alternating change between the water inrush growth area and the flow stable area with similar cyclic characteristics. The effect of dynamic load will increase the pore pressure in cracks, and increase the stress intensity factor at the crack tip, and more easily induce crack expansion and penetration failure. The critical water pressure calculation equation for crack propagation and failure under dynamic and static loads was derived, and the calculation method for the minimum safe thickness of the floor was further analyzed, the influence of water pressure, crack length, inclination angle, and mining depth on it was discussed. The effect of dynamic load will increase the pore pressure in cracks, and increase the stress intensity factor at the crack tip, and more easily induce crack expansion and penetration failure. Finally, the theoretical analysis results were verified by an engineering examples. The research results can provide theoretical basis for predicting and preventing water inrush from the mining floor, which is beneficial for the safe and sustainable mining of coal mines.